PE_PGRS3 of Mycobacterium tuberculosis is specifically expressed at low phosphate concentration, and its arginine‐rich C‐terminal domain mediates adhesion and persistence in host tissues when expressed in Mycobacterium smegmatis. (26th September 2018) - De Maio, Flavio; Battah, Basem; Palmieri, Valentina; Petrone, Linda; Corrente, Francesco; Salustri, Alessandro; Palucci, Ivana; Bellesi, Silvia; Papi, Massimiliano; Rubino, Salvatore; Sali, Michela; Goletti, Delia; et al.
Abstract: PE_PGRSs of Mycobacterium tuberculosis ( Mtb ) represent a family of complex and peculiar proteins whose role and function remain elusive. In this study, we investigated PE_PGRS3 and PE_PGRS4, two highly homologous PE_PGRSs encoded by two contiguous genes in the Mtb genome. Using a gene‐reporter system in Mycobacterium smegmatis ( Ms ) and transcriptional analysis in Mtb, we show that PE_PGRS3, but not PE_PGRS4, is specifically expressed under low phosphate concentrations. Interestingly, PE_PGRS3, but not PE_PGRS4, has a unique, arginine‐rich C‐terminal domain of unknown function. Heterologous expression of PE_PGRS3 in Ms was used to demonstrate cellular localisation of the protein on the mycobacterial surface, where it significantly affects net surface charge. Moreover, expression of full‐length PE_PGRS3 enhanced adhesion of Ms to murine macrophages and human epithelial cells and improved bacterial persistence in spleen tissue following infection in mice. Expression of the PE_PGRS3 functional deletion mutant lacking the C‐terminal domain in Ms did not enhance adhesion to host cells, showing a phenotype similar to the Ms parental strain. Interestingly, enhanced persistence of Ms expressing PE_PGRS3 did not correlate with increased concentrations of inflammatory cytokines. These results point to a critical role for the ≈ 80 amino acids long, arginine‐rich C‐terminal domain of PE_PGRS3 in tuberculosis pathogenesis.